2008
DOI: 10.1111/j.1442-2018.2008.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to cognitive status among elders in southern Thailand

Abstract: This study examined the prevalence of and risk factors predicting cognitive impairment among elders in southern Thailand. Four-hundred Thai elders were administered five interview-based questionnaires that assessed demographic characteristics, cognitive function, depression, independent activities of daily living, and social connections. Although most of the elders had normal cognitive function, approximately 15% experienced cognitive impairment. Though nine of the 10 risk factors examined were identified as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…We found significant gender disparities in cognitive function among a geographically diverse, representative sample of adults aged 45 years or older across four Indian states. Our results were consistent with a growing literature on cognitive health in developing countries that show women perform worse than men on cognitive measures (Lei, Hu, McArdle, Smith, & Zhao, 2011;Maurer, 2011;Taboonpong, Chailungka, & Aassanangkornchai, 2008;Yount, 2008). These results contrast with those in industrialized countries, where women typically outperform men (Langa et al, 2008(Langa et al, , 2009.…”
Section: Discussionsupporting
confidence: 91%
“…We found significant gender disparities in cognitive function among a geographically diverse, representative sample of adults aged 45 years or older across four Indian states. Our results were consistent with a growing literature on cognitive health in developing countries that show women perform worse than men on cognitive measures (Lei, Hu, McArdle, Smith, & Zhao, 2011;Maurer, 2011;Taboonpong, Chailungka, & Aassanangkornchai, 2008;Yount, 2008). These results contrast with those in industrialized countries, where women typically outperform men (Langa et al, 2008(Langa et al, , 2009.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with previous evidence from low‐ and middle‐income settings that have reported that older women perform on average worse on memory function measures than older men, 37–39 in contrast to high‐income settings, where older women typically outperform older men 40,41 . Consistent with our findings, previous research in India has found substantial gender gaps in later‐life cognition, with older Indian women having worse memory function than older Indian men 11,33 .…”
Section: Discussionsupporting
confidence: 92%
“…The residents of Punjab had better memory scores than the residents of Karnataka, while the residents of Kerala did worse than those of Karnataka. that showed that women performed worse than men on a variety of cognitive measures (Lei et al, 2011;Maurer, 2011;Taboonpong et al, 2008;Yount, 2008). These results contrast with what is observed in industrialized countries, where women typically outperform men (Langa et al, 2008(Langa et al, , 2009.…”
Section: Resultsmentioning
confidence: 82%